2021
DOI: 10.1177/0018578721999809
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Pharmacist-Led Opt-Out Cessation Treatment Protocol for Combustible Tobacco Smoking Within Inpatient Settings

Abstract: Background: Although people who smoke cigarettes are overrepresented among hospital inpatients, few are connected with smoking cessation treatment during their hospitalization. Training, accountability for medication use, and monitoring of all patients position pharmacists well to deliver cessation interventions to all hospitalized patients who smoke. Methods: A large Midwestern University hospital implemented a pharmacist-led smoking cessation intervention. A delegation protocol for hospital pharmacy inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This study is among the first to show a health systemwide EHR intervention can improve smoking cessation therapy prescription rates associated with hospitalisations. Results are consistent with findings from a pharmacist-led opt-out cessation treatment integrated into existing inpatient medical reconciliation workflows 18. Prior evidence has shown that NRT is underprescribed during hospitalisations regardless of the reason for admission 19.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study is among the first to show a health systemwide EHR intervention can improve smoking cessation therapy prescription rates associated with hospitalisations. Results are consistent with findings from a pharmacist-led opt-out cessation treatment integrated into existing inpatient medical reconciliation workflows 18. Prior evidence has shown that NRT is underprescribed during hospitalisations regardless of the reason for admission 19.…”
Section: Discussionsupporting
confidence: 81%
“…Results are consistent with findings from a pharmacist-led opt-out cessation treatment integrated into existing inpatient medical reconciliation workflows. 18 Prior evidence has shown that NRT is underprescribed Open access during hospitalisations regardless of the reason for admission. 19 A 2014 Cochrane review of EHR-embedded smoking cessation tools found no studies that showed an effect on prescriptions for smoking cessation medications.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The published literature includes many informative examples of how electronic health records can be used to identify patients who smoke and support smoking cessation interventions for patients with cancer and other types of patients seen in health care settings. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] As a result of this literature and feedback received from our patients, the HCC instituted an opt-out telehealth pharmacyassisted tobacco treatment program (TTP) as our primary mode for offering patients smoking cessation support. The TTP includes 4 components: (1) screening of electronic health records to identify patients who currently smoke and who were seen across 43 HCC outpatient oncology clinics; (2) opt-out referral of patients to the TTP for those who have not previously been offered the TTP in the past 6 months; (3) telephone outreach to patients to offer them the opportunity to enroll in the TTP which consists of up to 4 counseling calls and free smoking cessation nicotine replacement therapy medications mailed to their home for those deemed eligible for pharmacotherapy; and (4) follow-up evaluation which involves recontacting a random sample of referred patients 4 to 12 months after referral to the TTP to independently assess smoking status and collect feedback useful for ongoing quality improvement.…”
mentioning
confidence: 99%
“…It includes changing health information technology, integrating documentation into existing workflows, engaging clinical support staff, or increasing training to build staff capacity (Flocke et al, 2020). Health systems change innovations for tobacco treatment have been implemented and examined in hospitals (Trapskin et al, 2022), outpatient clinics (Baker et al, 2021; Flocke et al, 2020; Jansen et al, 2014; Thomas et al, 2017), oncology clinics (Gali et al, 2020), behavioral health sites (Bloom et al, 2018; Himelhoch et al, 2014), supervised injecting facilities (Skelton et al, 2019), integrated health systems (Jansen et al, 2014; Whittet et al, 2019), and dental clinics (Thomas et al, 2017; Whittet et al, 2019). Although health systems change innovations for tobacco treatment have been implemented across a range of settings, most studies examining such innovations are limited to one setting (Baker et al, 2021; Bloom et al, 2018; Flocke et al, 2020; Gali et al, 2020; Himelhoch et al, 2014; Skelton et al, 2019; Thomas et al, 2017; Trapskin et al, 2022).…”
mentioning
confidence: 99%
“…Health systems change innovations for tobacco treatment have been implemented and examined in hospitals (Trapskin et al, 2022), outpatient clinics (Baker et al, 2021; Flocke et al, 2020; Jansen et al, 2014; Thomas et al, 2017), oncology clinics (Gali et al, 2020), behavioral health sites (Bloom et al, 2018; Himelhoch et al, 2014), supervised injecting facilities (Skelton et al, 2019), integrated health systems (Jansen et al, 2014; Whittet et al, 2019), and dental clinics (Thomas et al, 2017; Whittet et al, 2019). Although health systems change innovations for tobacco treatment have been implemented across a range of settings, most studies examining such innovations are limited to one setting (Baker et al, 2021; Bloom et al, 2018; Flocke et al, 2020; Gali et al, 2020; Himelhoch et al, 2014; Skelton et al, 2019; Thomas et al, 2017; Trapskin et al, 2022). Furthermore, no study has examined TTS implementation as a specific component of health systems change nor applied a theoretical perspective to comprehensively examine factors that may influence sustainability of TTSs.…”
mentioning
confidence: 99%